Religions and trade religious formation, transformation, and cross-cultural exchange between East and West - Wick, Peter; Rabens, Volker, 1971- (Leiden, The Netherlands : Brill, 2014)
Religions and Trade carves new pathways into the world of religious dynamics. In this array of essays a number of international scholars investigate the ways in which eastern and western religions were formed and transformed from the perspective of "trade."
Trading Institutions: The Design of Daoist MonasticismPhilo's Attractive Ethics on the "Religious Market" of Ancient Alexandria; Traveling Ethics: The Case of the Household Codes in Ephesians 5:21-6:9 in Cross-Cultural Perspective; Index.
Includes bibliographical references and index.
Print version record.
Keywords: Religions; Religions -- Relations; Globalization -- Religious aspects; Commerce; Business -- Religious aspects; Business -- Religious aspects; Commerce; Globalization -- Religious aspects; Religions -- Relations; Religions; BODY, MIND & SPIRIT -- Gaia & Earth Energies; RELIGION -- Christianity -- General; Business -- Religious aspects; Commerce; Globalization -- Religious aspects; Religions; Religions -- Relations; Electronic books